GOVERNMENT AND NON-PROFIT ORGANISATIONS: DYSFUNCTIONAL STRUCTURES AND RELATIONSHIPS AFFECTING CHILD PROTECTION SERVICES - Van Niekerk, Joan; Matthias, Carmel (Social Work/Maatskaplike Werk, 2019)
<span style="font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-bidi-font-size: 14.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">This article is based on a qualitative descriptive study of the child protection system after 1994. Semi-structured interviews were conducted with senior social workers in management positions in the Department of Social Development and non-profit organisations in three provinces. The main focus of the article is on the structure, functioning and resourcing of child protection services in post-apartheid South Africa. Key findings of the study include the lack of an over-arching strategy for child protection services, the dysfunctional relationship between government and the non-profit sector, and inadequate resourcing,